Biobanking of human teeth for stem cell storage: preserving stem cells for future needs - Habib, Saqib; Khan, Shahrukh Ali; Ahmed, Aqeel; Khan, Farhan Raza (Journal of the Pakistan Medical Association, 2024)
Human teeth serve as a potential reservoir for post-embryonic mesenchymal dental stem cells. Researchers have identified and isolated seven types of dental stem cells from pulp and periodontal ligament tissues. These cells have a wide range of clinical applications across the fields of medicine and dentistry due to their increased proliferative nature. Biobanking is a concept for storing human biological tissues to preserve and isolate stem cells. Until now, haematopoietic tissues have been the area of focus for biobanking facilities. Extracted human teeth may serve as a valuable resource for the isolation and preservation of dental stem cells for future therapeutic benefits. The current narrative review was planned to focus on the workflow of the teeth biobanking process, its isolation, cryopreservation, and potential therapeutic uses in medical and dental specialties. Key Words: Stem cells, Biobank, Dental stem cells.